A Cultural Response to a Rural Crisis: Educational Films for Rural Society in INterwar China. Issue 2 (3rd April 2021) - Li, Kaiyi
Abstract : In the 1930s, educational film was a popular medium for mass education in Republican China, especially in rural society. This article argues that the use of educational film in rural China served not merely to increase the knowledge of the peasant population, but reflected a cultural response by the Chinese government to solving the rural crisis – a response that reflected the atmosphere of national zeal prevailing at that time. The article first analyses the discussion among Chinese politicians and scholars on the topic of the rural crisis and examines how mass education was adopted as a means of solving the problem. It then probes the question of why educational films became a popular tool among mass education teachers. Taking three films as examples, the article proposes that the information they contain emphasized their technical aspects but ignored the conflicts and corruption uncovered by the elites. A final section approaches the phenomenon of educational film from the perspective of the history of the socialization of rural society and of education in 1930s China, asserting that Chinese educational film at that time essentially provided a new medium for an old ideology.